(untitled) (XXI Century. Spanish Literature and Culture)
This essay proposes an approach to the realm of dreams in relation to poetry, and demonstrates how dreams are part of certain aspects of writing, and the poetic effectiveness of dream images in the text. In short, how does one explain a dream with words? This essay suggests possible solutions to this problem.